Co(II), Ni(II) and Cu(II) Chelates of Bis-9,10-Phenanthro-quinonedioxime and their Nitrogen-Donor adducts with NH3 and Pyridine - Rai, B.K.; Chaudhary, S.K.; Rai, H.C. (Asian Journal of Chemistry, 2010)
Metal chelates of 9,10-phenanthroquinonedioxime with Co(ll), Ni(II) and Cu(II) of the types M(HL)2 [M = Co(Il), Ni(II) and Cu(II)l, H2L = 9, 10-phenanthroquinonedioxime where H = dissociable oximato proton have been synthesised by allowing ethanolic solutions of metal salts to react with solution of the ligand in tetrahydrofuran in the molar ratio 1 : 2. They produce another series of metal chelates of the type [M(HL)2X2] (X = NH3 or pyridine) when their solution was treated with ammonia or pyridine. I,R spectrum suggests coordination of the ligand with metal ions through azomethime nitrogen in bidentate manner. Electronic spectral and magnetic moment studies indicate complexes of the type [M(HL)2] to be square planar and those of the type [M(HL)2X2] to be octahedral in nature.